How Government and Digital Innovation Enhance MSMEs' Income A Study of Kolaka Regency - Adinda Anggraini Ayustira; Fitri Kumalasari; Andry Stepahnie Titing (SEAN Institute, 2025)
This study investigates the influence of government support and digital innovation on the income of micro, small, and medium enterprises (MSMEs) in Kolaka Regency, Indonesia. Amidst the rapid evolution of the digital economy, MSMEs face both opportunities and challenges in adopting technology to enhance competitiveness and market access. Utilizing a quantitative research approach, data were collected through questionnaires distributed to 65 MSME actors selected via the Slovin formula. The research employed Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) method for data analysis. The results indicate that both government roles—encompassing facilitation, mobilization, and regulation—and digital innovation—through design changes, technical innovation, and product development—positively and significantly affect MSME income levels. The study highlights that technological adoption improves business efficiency, market outreach, and revenue performance. However, constraints such as limited digital literacy and inadequate infrastructure remain. The findings emphasize the importance of collaborative efforts among governments, private sectors, and educational institutions to provide training, technology access, and policy support. This integrated approach is essential to accelerating digital transformation and fostering sustainable economic growth through empowered MSMEs.